Serological detection of Citrus tristeza virus affecting Citrus tree species in Assam - A. K. SAIKIA, MUNMI BORAH*, P. D. NATH and (Indian Phytopathology, 2012)
Field surveys were carried out in 8 citrus growing districts of Assam (Tinsukia, Lakhimpur, Jorhat, Kokrajhar, North Cachar Hills, Karbi Anglong, Golaghat and Kamrup). Altogether 411 samples were collected from three different citrus species, viz., Assam lemon (Citrus limon), Gul nemu (Citrus jambhiri) and Khasi mandarin (Citrus reticulata). Typical symptoms of CTV (Citrus tristeza virus), namely, leaf yellowing and vein clearing were prominent. Incidence of CTV was more in matured and older plants. Survey results indicated prevalence of the vector Toxoptera citricida and Toxoptera aurantii in this region.Â The samples were tested for the presence of CTV by double antibody sandwich-enzyme linked immuno-sorbent assay (DAS-ELISA). The results showed 261 trees infected with CTV indicating 63.50 per cent diseases incidence in Assam. Results revealed presence of CTV in all the surveyed districts of Assam showing a high incidence of 78.04 per cent CTV infection in Karbi Anglong districts followed by 76.92 per cent in Golaghat district. Among the different citrus species Assam lemon showed a significantly high CTV infestation of 76.47 per cent followed Khasi mandarin (61.18%) and Gul nemu (52.03%). The results of DAS-ELISA revealed that in all the three different citrus species Assam lemon, Gul nemu and Khasi mandarin the percentage of positivity is more in the higher age group viz. > 15 years and 10-15 yearsÂ followed by lower age group (<10 year old plants). This indicated prevalence of CTV was more in older plants.